The Roles of SOCS in Teleost Immunity: Cytokine Regulation and Host Defense - Ying Zhang; Li Yang; Xiuying Cui; Feng Gao; Yanjing Zhao; Xianghui Kong (Reviews in Aquaculture, 2026)
The Suppressor of Cytokine Signaling (SOCS) family comprises key regulatory molecules which are essential for maintaining immune homeostasis in vertebrates. Owing to a teleost‐specific whole‐genome duplication event, SOCS family members exhibit higher diversity and significant functional differentiation, forming a complex and precise immune regulatory network. This review comprehensively summarizes the current understanding of SOCS‐mediated cytokine regulation and host defense mechanisms in teleosts. SOCS proteins, particularly SOCS1 and SOCS3, exert dual regulatory effects in antiviral and antibacterial immunity as well as in inflammatory balance by negatively modulating key pathways such as JAK/STAT and NF‐κB, exemplifying their “double‐edged sword” role. Moreover, we provide the first comprehensive synthesis of environmental regulation of SOCS expression in teleosts, integrating emerging evidence on how to modulate SOCS levels after temperature stress, neuroendocrine activation via cortisol, hypoxia, and chemical pollutants and how to link environmental conditions to immune competence. This environmental perspective supplies direct implications for understanding stress‐induced immunosuppression in aquaculture. Finally, we discuss the potential application of targeting SOCS signaling in aquaculture practices, including applications in disease‐resistant breeding, vaccine development, and immunostimulant design. In‐depth understanding of SOCS diversity and function in fish will provide novel molecular insights and innovative strategies for precise disease control and sustainable aquaculture.